DOCUMENTATION OF SANTRI’S ORAL CULTURAL OBJECTS IN PASURUAN CITY AS A PHILOLOGY LECTURE PROJECT - Tristan Rokhmawan; Badriyah Wilandari; M.Z. Arif Sungsang Maulana (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Pasuruan City has a lot of local wisdom in the form of folklore. This is evidenced by the results of the project for documenting various folklore, which is briefly presented in this article. Various types of folklore were collected by the author, together with the research team and folklore documentation of the elements of the Indonesian Language Study Program student STKIP PGRI Pasuruan, consisting of 170 folklore. The collected folklores are verbal and half oral. The documented folklor are then classified in 10 different themes including: 1) Legend of Islamic Figures, 2) Legend of Village Origins, 3) Mystery Stories in Pesantren Life, 4) Myths related to Animals, 5) Material-related Myths as Intermediaries of Prayer, 6) Myths related to Objects in Funeral Rituals, 7) Praise Poems Chanted by the Santri Community, 8) Practices in Ritual Recitation, and 9) Habitual Practices in Santri Life in Islamic Boarding Schools. These forms of folklore at the same time show the form of traditional orality in the lives of Muslim communities in Pasuruan City. The folklore research that develops in a community has several benefits such as: (1) preserving the culture of community orality, (2) increasing public awareness of the preservation of the culture of orality, (3) raising the descriptive framework of oral culture and culture in general which is owned by a community , (4) revitalizing the cultural functions of orality that have been developed in a society, (5) providing research material for academics in language and culture, and (6) iconic support for the city branding of Pasuruan City.